Intraductal radiofrequency ablation plus biliary stent versus stent alone for malignant biliary obstruction: a systematic review and meta-analysis - de Oliveira Veras, Matheus; de Moura, Diogo Turiani Hourneaux; McCarty, Thomas R.; de Oliveira, Guilherme Henrique Peixoto; Gomes, Rômulo Sérgio Araújo; Landim, Davi Lucena; Nunes, Felipe Giacobo; Franzini, Tomazo Antônio Prince; Lera dos Santos, Marcos Eduardo; Bernardo, Wanderley Marques; de Moura, Eduardo Guimarães Hourneaux (Endoscopy International Open, 2024)
Background and study aims Recurrent biliary stent occlusion and tumor ingrowth remain a major concern among patients with malignant biliary obstruction (MBO) with significant impact on patient morbidity and survival. Intraductal radiofrequency ablation (RFA) has emerged as a promising treatment that seeks to extend stent patency. This study aimed to evaluate the impact of RFA on overall survival (OS) and stent patency among patients with unresectable MBO.Methods A comprehensive search of electronic databases was performed for randomized controlled trials (RCTs) comparing RFA plus biliary stent (RFA+S) versus biliary stent alone (S-alone). Outcomes assessed included overall survival, stent patency, and adverse events (AEs) with mean difference (MD) calculated from pooled proportions. Subgroup analyses were performed for hilar strictures and cholangiocarcinoma (CCA).Results Six RCTs (n=481 patients) were included and demonstrated improved survival among patients who received RFA+S (MD 85.70 days , 95% confidence interval [CI] 34.29–137.10; I2=98%; P =0.001). The pooled MD for total stent patency was 22.25 days (95% CI –17.38–61.87; I2=97%; P=0.27). There was no difference in AEs between RFA+S vs S-alone (P >0.05). On subgroup analyses, RFA+S was associated with improved stent patency (MD 79.25 days; 95% CI 50.77–107.73; I2=59%; P <0.00001) and OS (MD 83.14 (95% CI 29.52–136.77; I2=97%; P <0.01] for CCA. For hilar strictures, stent patency was improved among patients with RFA+S [MD 83.71 days (95% CI 24.85–142.56; I2=84%; P <0.01].Conclusions RFA+S improved OS in the treatment of MBO when compared with S-alone. Moreover, the RFA therapy prolonged stent patency in hilar strictures and CCA, with similar rates of AEs.
Keywords: Strictures; PTCD/PTCS